Exploring Jalaluddin Rumi's Philosophy of Love through YouTube Content ‘Ngaji Filsafat’ on MJS Channel - Ningrum, Velida Apria; Muhyin, Nabila Fajriyanti; Velida Apria Ningrum (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2024)
Currently, the YouTube platform has become the primary source of information and entertainment for many people. The YouTube platform offers a variety of engaging educational content, including content related to the study of philosophy. ‘Ngaji Filsafat’ is a segment that has been around for 10 years on the MJS Channel and has consistently presented philosophy discussions in a light and engaging manner. Episode 144, which explores the philosophy of love by Jalaluddin Rumi, became the most popular episode with 1.6 million viewers. This article aims to uncover how delivering content through this platform can influence the audience's perception and understanding of Rumi's philosophy of love. This research utilizes a qualitative approach, with data collection methods involving observation and document analysis. The collected data will be analyzed descriptively and analytically using the Miles and Huberman analysis model. The study indicates that delivering the concepts of Jalaluddin Rumi’s philosophy of love through the ‘ngaji filsafat’ content can enhance and deepen the viewers insights on the MJS Channel YouTube platform.